First record of Neorthostigma Belokobylskij (Hymenoptera: Braconidae: Alysiinae) from Neotropical region with description of two new species - de Oliveira, Franciélle Dias; Penteado-Dias, Angélica Maria (Zootaxa, 2023)
The genus Neorthostigma Belokobylskij, 1998 is recorded in the Neotropical region for the first time, with description of two new species from Brazil viz. Neorthostigma neotropicalis sp. nov. and Neorthostigma signifrons sp. nov. A dichotomous identification key for the known species of Neorthostigma is provided.